Production Performance of Broilers Fed with Crude Rice Bran Oil - Anitha, B.; Moorthy, M.; Viswanathan, K. (International Journal of Poultry Science, 2006)
An experiment was conducted to study the inclusion of crude rice bran oil on production performance, carcass characteristics and biochemical parameters for a period of seven weeks with two hundred and sixteen commercial, straight run day-old Vencobb broiler chicks. These chicks were randomly grouped into six treatments with three replicates of twelve chicks each. The treatment groups consisted of 0 percent (T1), 1 percent (T2), 2 percent (T3), 3 percent (T4), 4 percent (T5) and 5 percent (T6) crude rice bran oil included in the broiler diet. The results revealed that there was no significant difference in body weight and body weight gain between treatment groups from first week to end of the experiment period except at second week (P< 0.05). Similarly, no significant difference was recorded in feed consumption, feed conversion ratio and carcass yields, but in feed conversion ratio significant (P< 0.05) difference was recorded at second week of age. Livability was 100 percent in all the treatment groups except in T6 wherein mortality of one bird was observed during seventh week of age. The abdominal fat percentage revealed no significant difference among various treatment groups by inclusion of crude rice bran oil. The breast muscle cholesterol revealed no significant difference between treatment groups. Whereas the mean thigh muscle cholesterol of other treatment group birds was significantly (P< 0.05) lower than those of control group. The serum total cholesterol, HDL cholesterol, LDL cholesterol and triglycerides level did not differ significantly between treatment groups. The return over feed cost did not differ significantly between treatment groups except at second week of age. Based upon this study, it is concluded that the inclusion of crude rice bran oil up to 3 percent in broiler ration is recommended for better growth and high return over feed cost.